Analisis penghindaran pajak, beban pajak tangguhan, dan koneksi politik terhadap manajemen laba - Riky Antonius; Lambok DR Tampubolon (Jurnal Akuntansi, Keuangan, dan Manajemen, 2019)
Purpose: This study aims to examine the effect of tax avoidance, deferred tax burden and political connections on earnings management. Research methodology: Purposive sampling was used as the sampling technique in this study. The data was tested using multiple-linear regression. Results: The results show that tax avoidance, deferred tax expense, and company’s political relation have no effect on earnings management practice. Limitations: A limitation of this study is the use of very little data due to the large number of sampling criteria. Contribution: This study can be a reference for companies to make better earnings management. Keywords: Tax avoidance, Deferred tax expense, Political relation, Company size, Leverage, Return on assets, Earnings management